The Role of Strategic direction in Strategic Reputation and its impact on Competitive Compressions Survey study in mobile communications companies in Iraq - حسين, علي كاظم (Journal of Economics and Administrative Sciences, 2019)
Obstruct:                                                                                                                                 The current research aims at identifying the role strategic Orientation of the dimensions (market orientation, customer orientation, Entrepreneurship orientation, competitor orientation, technology orientation) in strategic reputation building in its dimensions (product and service quality, financial performance, environment and workplace, Innovation, Social Responsibility), and its effect on competitive pressure with its two dimensions (Internal and External Pressure), to accomplish the research aim (Zain, Iraq, Asia Cell, Cork, Omnia) have been chosen in the province of Karbala, as the research tries to identify the role of the intellectual and practical framework to played by the direction started from a problem expressed by a number of intellectual and practical questions aimed to answer and diagnose the level of their importance, their impact and the extent of their applicability in the telecommunications companies. The research is based on the questionnaire form as a tool for collecting the necessary data. The research sample reaches (89) managers in the companies, and obtained (81) questionnaire forms valid for analysis. One of the most important conclusions is the lack of discrepancy between the dimensions of the companies in question with regard to attracting customers and care of the quality of services provided. The important recommendations needed to be adopted is proactive strategy consistent with the capabilities of companies promise to impose a strategic as a context of competitive influence.